Navigating Drug Dynamics: Unleashing On-Chip Pharmacokinetics and Pharmacodynamics - Das, Anish Kumar; Mutukuri, Rakesh; Chowdhury, Neelanjan; Paul, David; Nanjappan, Satheesh Kumar (Drug Metabolism and Bioanalysis Letters, 2025)
Accurate prediction of Absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) is a key component in using the drug as a therapeutic. Traditionally many in vitro and in vivo techniques are used for ADMET profiling in pre-clinical studies. Due to the absence of all cellular parameters and inter-species variability, the obtained pre-clinical study results were not reproducible in clinical trials. As a result, both industry and academic researchers find drug discovery and development to be a daunting task due to several constraints. A reliable and simple approach is, therefore, needed for in vitro PK-PD studies. The new ray of hope in this field is the Organ-on-a-Chip (OoC) technique. On one side, it is an in vitro technique, and on another side, it can reliably produce reliable PK/PD results. In this review, we primarily focused on the application and scope of OoC technology in the field of PK/PD studies. We believe this review will be helpful for future researchers in this domain.
Keywords: microphysiological systems